2009
DOI: 10.1111/j.1476-5381.2009.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic characteristics of imatinib resistance in chronic myeloid leukaemia cells

Abstract: Background and purpose: Early detection of resistance development is crucial for imatinib-based treatment in chronic myeloid leukaemia (CML) patients. We aimed to distinguish metabolic markers of cell resistance to imatinib. Experimental approach: Two human imatinib-sensitive CML cell lines: LAMA84-s and K562-s, and their resistant counterparts: LAMA84-r and K562-r (both resistant to 1 mM imatinib), and K562-R (5 mM) were analysed by nuclear magnetic resonance spectroscopy to assess global metabolic profiling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…However, the evaluation of the mean quantity of drug in each cell showed that the intracellular concentration was markedly higher than the extracellular concentration, indicating a predominantly active mechanism (13,25). Although this process is not fully understood, it probably involves a saturable-type transporter (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evaluation of the mean quantity of drug in each cell showed that the intracellular concentration was markedly higher than the extracellular concentration, indicating a predominantly active mechanism (13,25). Although this process is not fully understood, it probably involves a saturable-type transporter (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, imatinib treatment of chronic myeloid leukemia cells induces a shift from glycolysis to mitochondrial metabolism, a phenotype associated with non-cancerous tissues (90,91). Imatinib-resistant cells display no such decrease in glycolysis in response to drug treatment.…”
Section: Applications Of Sirm In Drug Developmentmentioning
confidence: 99%
“…Previous studies have investigated altered glucose metabolism in chemoresistant leukemia cells (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). It has been reported that prednisolone resistance in patients with precursor B-cell acute lymphoblastic leukemia (ALL) was associated with an increased expression of genes involved in glucose metabolism (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that prednisolone resistance in patients with precursor B-cell acute lymphoblastic leukemia (ALL) was associated with an increased expression of genes involved in glucose metabolism (5,6). Imatinib-resistant chronic myelogenous leukemia cells also exhibited a high glycolysis phenotype, with elevated glucose uptake and lactate production compared with imatinib-sensitive cells (7)(8)(9)(10). In addition, AML cell lines with an increased level of glycolysis showed increased resistance to the induction of apoptosis in vitro due to a combination of all-trans retinoic acid and arsenic trioxide (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation